Health system architecture and its role for economic perspective of wellbeing - Jagrič, Timotej (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2022)
Wellbeing from an economic perspective is about getting access to quality healthcare when needed to enable a quality life and healthier and more productive workforce in the economic ecosystem, thus contributing to economic growth. In this analysis we try to identify, what type of the architecture in the health care system can promote wellbeing.
Keywords: health system; market failures; health providers; health insurance